2003
DOI: 10.1111/j.1399-543x.2003.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and its interrelation with family environment and metabolic control in Turkish adolescents with type 1 diabetes

Abstract: In the present study, there was no relationship between self-efficacy, family environment, and metabolic control in the total sample, but in girls, self-efficacy and family cohesion was positively correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
12
2
1
Order By: Relevance
“…In the present study a substantial number of patients (43–60%) stated that insulin therapy would cause family and friends to be more concerned about them, whereas Polonsky et al. [6] did not report this response, possibly related to differences in culture [15,16].…”
Section: Discussioncontrasting
confidence: 59%
“…In the present study a substantial number of patients (43–60%) stated that insulin therapy would cause family and friends to be more concerned about them, whereas Polonsky et al. [6] did not report this response, possibly related to differences in culture [15,16].…”
Section: Discussioncontrasting
confidence: 59%
“…[50] The study by Pinar on diabetic patients showed that factors like intimacy among family members, existence or lack of existence of conflict in the family, and current affective status of the family can affect the self-efficiency of patients and can lead to increase of self-efficiency and decrease of stress in the family. [51]…”
Section: Resultsmentioning
confidence: 99%
“…Sex is another important demographic variable that should be considered in future studies. It is unclear whether there are sex differences in self‐care or glycemic control (Helgeson, Lopez et al., 2009; Pereira, Berg‐Cross, Almeida, & Machado, 2008; Pinar, Arslanoglu, Isgüven, Cizmeci, & Gunoz, 2003). However, it is clear that sex may moderate some of the relations between psychosocial factors and diabetes outcomes.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%